Hubungan Pelayanan Antenatal Care 10 T dengan Kepuasan Ibu Hamil di Puskesmas Biru-Biru Tahun 2025 - Betty Mangkuji; Jujuren Sitepu; Chandra Juita Pasaribu (Pusat Riset dan Inovasi Nasional, 2025)
Antenatal Care (ANC) is a health service provided to pregnant women during pregnancy by healthcare professionals in accordance with established standards, one of which is the implementation of the 10T ANC service components. The quality of ANC services plays an important role in determining pregnant women’s satisfaction, which in turn affects their compliance with antenatal visits and the effectiveness of pregnancy monitoring. Maternal satisfaction is an essential indicator for assessing the quality of healthcare services at primary healthcare facilities. This study aimed to examine the relationship between 10T Antenatal Care services and pregnant women’s satisfaction at Biru-Biru Public Health Center in 2025. This research employed a quantitative method with an analytical design using a cross-sectional approach. The sample was selected through purposive sampling, involving 48 third-trimester pregnant women. Data were collected using questionnaires that assessed the implementation of 10T ANC services and the level of maternal satisfaction. The collected data were analyzed statistically to determine the relationship between the variables. The findings of this study are expected to provide insights into the importance of optimal implementation of 10T ANC standards. Therefore, healthcare providers, particularly midwives, are encouraged to continuously improve the quality of ANC services to enhance pregnant women’s satisfaction and support efforts to improve maternal and child health outcomes.